2011
DOI: 10.2478/s13545-011-0046-z
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition of herring (Clupea harengus L.) and cod (Gadus morhua L.) in the southern Baltic Sea in 2007 and 2008

Abstract: Diet composition of two commercial fish species, herring and cod, were studied in some regions (mainly Gdańsk and Bornholm Basins, and the Polish coast) of the southern Baltic Sea in 2007 and 2008. Herring is the dominant zooplanktivorous species in the ecosystem of the Baltic Sea, but apart from mesoplanktonic organisms it also eats macroplanktonic and benthic species in considerable amount. The diet of cod consists of fish and crustaceans from pelagic, hyperbenthic and benthic habitats. The feeding preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Cod are predators that feed mainly on fish from the families Clupeidae , cod fry, and benthic crustaceans, and they are even cannibalistic. Herring feed on phytoplankton and zooplankton, small crustaceans and larval fish, while sprat feed on phytoplankton (Casini et al 2004 ; Dziaduch 2011 ; Beldowska et al 2015 ). The highest concentrations of mercury were confirmed in eel and cod tissues and organs, and CH 3 Hg + dominated in the muscle and liver, but it also occurred at high levels in other internal organs (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cod are predators that feed mainly on fish from the families Clupeidae , cod fry, and benthic crustaceans, and they are even cannibalistic. Herring feed on phytoplankton and zooplankton, small crustaceans and larval fish, while sprat feed on phytoplankton (Casini et al 2004 ; Dziaduch 2011 ; Beldowska et al 2015 ). The highest concentrations of mercury were confirmed in eel and cod tissues and organs, and CH 3 Hg + dominated in the muscle and liver, but it also occurred at high levels in other internal organs (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In spring, both Baltic sprat and herring prey mainly on copepods (Möllmann et al, 2004). In summer and autumn, sprat additionally feed on cladocerans while larger herring in autumn and winter favour mysids, amphipods, and polychaetes (Casini et al, 2004), although herring have also been observed to prey on cladocerans during autumn (Dziaduch, 2011). The main copepod species in the Baltic Sea are the calanoid copepods; Pseudocalanus sp., Temora longicornis, and Acartia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the North Sea, in the Baltic Sea stomach sampling has been conducted on a relatively regular basis, at least with regard to the commercially most important demersal fish species, Atlantic cod Gadus morhua (e.g., Arntz, 1974Arntz, , 1977Casini et al, 2016;Dziaduch, 2011;Hüssy et al, 1997;Pachur & Horbowy, 2013;Schulz, 1987Schulz, , 1988Schulz, , 1989aSchulz, , 1989bWeber & Damm, 1991;Zarkeschwari, 1977). Cod is considered the apex predator in the Baltic Sea, and major efforts were invested to improve the understanding of its trophic role.…”
mentioning
confidence: 99%
“…The main distributional areas of the two cod stocks differ remarkably in oceanographic conditions and also in prey availability and composition. In the past decades the diet studies mainly focused on the role of EBC in the eastern Baltic food web (e.g., Casini et al, 2016;Dziaduch, 2011;Hüssy et al, 1997;Kulatska et al, 2019;Pachur & Horbowy, 2013). These studies revealed that currently EBC relies strongly on Clupeid prey species such as herring Clupea harengus and sprat Sprattus sprattus,…”
mentioning
confidence: 99%